Observations on the influence of seasonality, lunar cycles, and weather condition on freshwater turtle activity in Sarawak, East Malaysia (Borneo) - Jensen, Karen A.; Das, I. (Asiatic Herpetological Research Society, 2008)
Freshwater turtles were surveyed at two sites in Sarawak: Loagan Bunut National Park and Balai Ringin. Capture results were tested against environmental factors such as lunar phase, weather and seasonality to examine differences in activity level. Proportionally, soft-shelled turtles were most active during the full moon (29.0%) and the last quarter lunar phase (29.4%). Hard-shelled turtles were active during the full moon 50.0% of the time. Both soft-shelled and hard-shelled turtles were more active during overcast periods (53.0% and 66.0%, respectively). Seasonality did not seem to affect soft-shelled turtle activity, while hard-shelled turtles were active 50.0% of the time during the dry South-west Monsoon from June to September.